EFFECT OF ADHESIVE ON MICRO SHEAR BOND STRENGTH OF A NEW BIOACTIVE, RESTORATIVE MATERIAL ON NORMAL AND CARIES-AFFECTED DENTINE - Zehra Süsgün Yıldırım; Ezgi Sonkaya (Cumhuriyet University, 2022)
ABSTRACT Objectives: Activa BioActive-Restorative is defined as a self-adhesive dual-cured resin-modified glass ionomer. The suggested application method includes only conditioning to the dentine with acid and keeps bonding optional. This study aims to evaluate the micro shear bond strength in the presence and absence of the bonding agent application after acid conditioning for different dentin surfaces. Materials and Methods: 30 posterior molars having occlusal caries were used. The flat dentin surfaces involving normal dentin (ND) and caries affected dentin (CAD) were prepared and randomly divided into three groups: Activa BioActive-Restorative (Pulpdent, USA) with only 10 seconds of acid application (Act), Activa with acid and bonding application (Optibond All in one, USA) (Act B), GC G-aenial Universal posterior composite with acid and bonding application (GC, Japan). A total of 6 groups were formed, as each group had normal and caries-affected dentin surfaces. Universal test machines were used to calculate micro shear bond strength at a crosshead speed of 0.5 mm/min, and failure modes were determined by stereomicroscope. Results: There was no statistically significant difference between test values of each group neither for ND (p:0,065; p>0,05) nor for CAD (p:0,110; p>0,05). There is no statistically significant difference between μ-SBS values of the ND and CAD subgroup for any of the groups (Act p:0,933; Act B p:0,684; GC p:0,863; p>0,05). Adhesive failure dominated the other failure modes. Conclusions: There is no difference between adherence of the material to ND and CAD. Acid application is sufficient for adequate binding. However, an optional bond application can be recommended, especially for dentin cavities. Keywords: Micro shear bond strength, bioactivity, adhesion